Spontaneous recovery of immune checkpoint inhibitor‐induced thyroiditis with high free T4 level: A case report. Issue 9 (7th September 2021) - Hagiwara, Rie; Suzuki, Daisuke; Tonezawa, Shiori; Saikawa, Rika; Funazaki, Shunsuke; Yoshida, Masashi; Washino, Satoshi; Miyagawa, Tomoaki; Hara, Kazuo; Yamada, Hodaka
Abstract: We describe a case of severe hyperthyroidism with high free thyroxine and C‐reactive protein levels, wherein thyroid function rapidly improved without treatment. In a similar case, conservative management with imaging follow‐up can be considered. Abstract : We describe a case of severe hyperthyroidism with high free thyroxine and C‐reactive protein levels, wherein thyroid function rapidly improved without treatment. In a similar case, conservative management with imaging follow‐up can be considered.